Molecular and serologic detection of Ehrlichia spp. in Endangered Brazilian wild captive felids - André, M. R. [UNESP]; Adania, C. H.; Machado, R. Z. [UNESP]; Allegretti, S. M.; Felippe, P. A.N.; Silva, K. F. [UNESP]; Nakaghi, A. C.H. [UNESP] (Wildlife Disease Association, 2010)
Ehrlichiosis, an emergent tickborne disease that affects both humans and animals, may represent a threat to the survival and preservation of wild felids in Brazil. There are few studies of ehrlichiosis in wild felids in Brazil, but Ehrlichia spp. are present in domestic cats. Antibodies to Ehrlichia canis have been reported in a puma (Puma concolor). In this study we assessed the presence of these hemoparasites in the blood of Brazilian wild captive felids. Of the 72 animals tested, 5 (7%) were seropositive for the E. canis antigen, and 11 (15%) were positive for E. canis DNA sequences. We also performed sequence alignment to establish the identity of the parasite species infecting these animals using 16S rRNA and omp-1 genes. Sequences based on 16S rRNA were similar to those found in dogs and cats from Thailand, Brazil, China, and Taiwan and with E. canis obtained from a single individual (human) in Venezuela. Ehrlichia sp. sequence from sampled felines based on omp-1 gene was similar to the p28 and p30 multigene family of E. canis. To our knowledge, this is the first study of molecular detection of Ehrlichia sp. in Brazilian wild feline species. © Wildlife Disease Association 2010.
Keywords: Brazil; Ehrlichia sp; PCR; Serology; Wild felids